2017
DOI: 10.1117/1.jbo.22.2.026001
|View full text |Cite
|
Sign up to set email alerts
|

Automated three-dimensional registration and volume rebuilding for wide-field angiographic and structural optical coherence tomography

Abstract: , "Automated three-dimensional registration and volume rebuilding for wide-field angiographic and structural optical coherence tomography," J. Biomed. Opt. Abstract. We propose a three-dimensional (3-D) registration method to correct motion artifacts and construct the volume structure for angiographic and structural optical coherence tomography (OCT). This algorithm is particularly suitable for the nonorthogonal wide-field OCT scan acquired by a ultrahigh-speed swept-source system (>200 kHz A-scan rate). First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Do 7 (2016, master’s thesis, Section 9) found that our method is more robust to fast microsaccadic eye movements than previous 2D strip-wise approaches. 12 , 13 Our method is also simpler than some previous approaches in that it does not require identification of specific features (e.g., blood vessels for feature-based registration 47 49 ) or segmentation of particular retinal layers to estimate eye motion, making it readily applicable to raster-scanned OCT images. This consideration should also make our approach more robust to retinal deformation caused by, e.g., edemas or drusen that make both layer segmentation and feature identification more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Do 7 (2016, master’s thesis, Section 9) found that our method is more robust to fast microsaccadic eye movements than previous 2D strip-wise approaches. 12 , 13 Our method is also simpler than some previous approaches in that it does not require identification of specific features (e.g., blood vessels for feature-based registration 47 49 ) or segmentation of particular retinal layers to estimate eye motion, making it readily applicable to raster-scanned OCT images. This consideration should also make our approach more robust to retinal deformation caused by, e.g., edemas or drusen that make both layer segmentation and feature identification more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The principle behind is sequential B-scan images over same retinal location, with subsequent analysis of change in amplitude and phase, inferred as flow of red blood cells in vasculature [3]. This cube scan generates a 3-dimensional image set and its extension provides en-face view of the vasculature at different layers of the retina [4]. Therefore, a flow-based imaging is available on top of the intensity-based B-scan imaging [5].…”
Section: Introduction Optical Coherence Tomography Angiographymentioning
confidence: 99%
“…Some methods additionally allow mosaicing of partially overlapping volumes [23,24], but are limited to alignment in the en face plane. Others allow full 3-D alignment including the axial dimension [21,[25][26][27][28]. A fundamental differentiation between software methods is the underlying scan pattern.…”
Section: Introductionmentioning
confidence: 99%